RARE FINDINGS OF MULTINODULAR GOITRE ON LUNG PERFUSION SCINTIGRAPHY OF A PATIENT WITH MALIGNANT MESOTHELIOMA - Zanial, Ahmad Zaid; Yeen, Boey Ching; Hassan, Siti Zarina Amir (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Malignant mesothelioma is an aggressive cancer of thoracic pleural lining that often requires urgent attention and management. Any other underlying diseases or comorbidities such as thyroid disorder could influence overall patient care and outcome. Lung perfusion scintigraphy performed using radionuclide-labelled tiny particles of macroaggregated albumin (5-100 microns) may facilitate pre-operative differential lung function evaluation. We report and illustrate incidental findings of increased tracer uptake by multinodular goitre (MNG) on lung perfusion scintigraphy in a malignant mesothelioma patient. RESULTS 63-year-old male, a chronic heavy smoker with underlying diabetes mellitus and hypertension presented with left pleural effusion. He was further managed and investigated. HPE of pleural biopsy (February 2019) confirmed features of malignant mesothelioma. As the pre-operative pulmonary spirometry test showed restrictive pattern, he was then referred for lung perfusion scintigraphy (April 2019) to determine differential function of right and left lung respectively which demonstrated severely reduced perfusion of the entire left lung. Incidental findings of increased tracer uptake also seen in the neck corresponding to an enlarged left thyroid lobe and multiple hypodense thyroid nodules; no gastric uptake visualised to indicate free pertechnetate and no renal activities noted to suggest right to left heart shunting. Quality control records showed good radiopharmaceutical labelling. Possible explanations include higher circulating tracer in view of the severely reduced left lung function and subclinical hyperthyroidism state. Upon further enquiry, we noticed that his prior imaging studies including the contrasted CT scan (January 2019) and fluorodeoxyglucose positron emission tomography scan (March 2019) had revealed features of MNG with retrosternal extension of the left lobe. CONCLUSION To our best knowledge, this is the first reported case of radionuclide-labelled macroaggregated albumin uptake by MNG in a patient with malignant mesothelioma. Biochemical correlation was suggested as this may help to ascertain possible additional comorbidity.